Safety of 3 Tesla Magnetic Resonance Imaging in Patients With Auditory Brainstem Implants. Issue 2 (30th November 2021) - Wichova, Helena; Peng, Kevin; Ledbetter, Luke; Slattery, William; Brackmann, Derald; Lekovic, Gregory
Abstract : Objective: To evaluate the safety of 3 Tesla (T) magnetic resonance imaging (MRI) in patients with auditory brainstem implants (ABI) with the magnet removed at implantation and report incidence of complications. Study Design: Retrospective chart review. Setting: Tertiary neurotology ambulatory practice. Patients: Patients with diagnosis of Neurofibromatosis, type 2 (NF2) with functional ABIs. Intervention(s): Observational recordings. Main Outcome Measure(s): Of the 89 patients meeting inclusion criteria, 7 patients underwent 3T MRI, with a total of 39 scans done. Three patients had 1 scan each, one patient had 4 scans, one patient had 5 scans, one patient had 6 scans, and one patient had 21 scans. The mean time between ABI placement and first 3 T scan was 118 ± 73 months. The most common indication for imaging was surveillance of NF2 lesions. The most frequent scans were MRI brain (25.6%), followed by MRI of cervical (15%), thoracic (15%) and lumbar (15%) spine, and MRI IAC (8%). There were no reported complications for any of the scans. No scans were interrupted due to patient discomfort. There were no device malfunctions. Conclusions: 3 T MRIs are safe in patients with ABIs as long as the magnet is removed. It is recommended that the magnet be removed at the time of implantation in all NF2 patients, who require frequent surveillance.